2018
DOI: 10.1016/j.ssmph.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Socioemotional wellbeing of mixed race/ethnicity children in the UK and US: Patterns and mechanisms

Abstract: Existing literature suggests that mixed race/ethnicity children are more likely to experience poor socioemotional wellbeing in both the US and the UK, although the evidence is stronger in the US. It is suggested that this inequality may be a consequence of struggles with identity formation, more limited connections with racial/ethnic/cultural heritage, and increased risk of exposure to racism.Using data from the UK Millennium Cohort Study (n = 13,734) and the US Early Childhood Longitudinal Study-Birth Cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…All analyses use sample weights to adjust for unequal probability of being sampled and the stratified and clustered sample design. As with other comparative studies (Nazroo et al 2018;Washbrook et al 2012;Zilanawala et al 2015a), we can use the standardized developmental outcomes of the average adolescent in each country as a benchmark relative to which their ethnic minority peers in each country can be assessed. Tables 1 and 2 present mean inequalities in early adolescent cognitive and socioemotional development and explanatory factors by race/ethnicity subgroup for the United Kingdom and United States, respectively.…”
Section: Planned Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…All analyses use sample weights to adjust for unequal probability of being sampled and the stratified and clustered sample design. As with other comparative studies (Nazroo et al 2018;Washbrook et al 2012;Zilanawala et al 2015a), we can use the standardized developmental outcomes of the average adolescent in each country as a benchmark relative to which their ethnic minority peers in each country can be assessed. Tables 1 and 2 present mean inequalities in early adolescent cognitive and socioemotional development and explanatory factors by race/ethnicity subgroup for the United Kingdom and United States, respectively.…”
Section: Planned Analysesmentioning
confidence: 99%
“…All analyses use sample weights to adjust for unequal probability of being sampled and the stratified and clustered sample design. As with other comparative studies ( Nazroo et al 2018 ; Washbrook et al 2012 ; Zilanawala et al. 2015a ), we can use the standardized developmental outcomes of the average adolescent in each country as a benchmark relative to which their ethnic minority peers in each country can be assessed.…”
Section: Datamentioning
confidence: 99%
“…However, some research indicates that there are no observed wellbeing differences by gender until relationship factors such as family, peers and school connectedness are introduced (Patalay & Fitzsimons, 2016). Similarly, research suggests that there are no differences in subjective wellbeing according to ethnicity (Nazroo et al, 2018). Wellbeing has been shown to decrease as young people get older (Children’s Society 2020) and young people in care report lower wellbeing than young people not in care (Long et al, 2017).…”
Section: Introductionmentioning
confidence: 99%